2016
DOI: 10.1016/j.arr.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism: A review of how ageing disrupts the biological mechanisms responsible for its regulation

Abstract: Cholesterol plays a vital role in the human body as a precursor of steroid hormones and bile acids, in addition to providing structure to cell membranes. Whole body cholesterol metabolism is maintained by a highly coordinated balancing act between cholesterol ingestion, synthesis, absorption, and excretion. The aim of this review is to discuss how ageing interacts with these processes. Firstly, we will present an overview of cholesterol metabolism. Following this, we discuss how the biological mechanisms which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 243 publications
1
80
0
5
Order By: Relevance
“…The modifications of cholesterol metabolism associated with ongoing age are still ill‐defined, partly because of the paucity of direct experimental data on lipid pathophysiology. Such alterations have been recently reviewed …”
Section: Age‐associated Changes In Cholesterol Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The modifications of cholesterol metabolism associated with ongoing age are still ill‐defined, partly because of the paucity of direct experimental data on lipid pathophysiology. Such alterations have been recently reviewed …”
Section: Age‐associated Changes In Cholesterol Homeostasismentioning
confidence: 99%
“…Such alterations have been recently reviewed. 9 Epidemiological studies have shown a trend towards an increase in plasma total and low-density lipoprotein (LDL) cholesterol with aging; [10][11][12] this is particularly evident from middle age to the seventh decade. In the very old, cholesterol levels tend to plateau or even decrease.…”
Section: Age-associated Changes In Cholesterol Homeostasismentioning
confidence: 99%
“…In total, 126 GWAS have been performed on CHL related phenotypes in humans and animal model species (https://www.ebi.ac.uk/gwas/search?query=cholesterol, accessed on 09 th January, 2018). Although mechanisms regulating CHL have been intensively studied in humans 1518 , few studies have been devoted to the genetics of CHL in livestock species. In cows, several gene expression/proteomics studies have reported genes with potential involvement in milk CHL concentration/metabolism 1927 but their actual roles and associated SNPs with CHL content in milk have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Of the diseases associated with advancing age, CVD is the leading cause of morbidity in individuals over 60 years of age (3) . The dysregulation of cholesterol metabolism is intimately associated with the pathogenesis of CVD (4) , and age-related alterations in the metabolism of cholesterol are implicated in the disturbance of this system (5) . These include, a decrease in LDL-cholesterol clearance; a potential increase in cholesterol absorption; a decrease in bile acid synthesis; a decrease in bacterial bile acid modification (6)(7)(8) .…”
mentioning
confidence: 99%